Specific and continuous training for all health care professionals along the survival chain! Thesis 6 of the Bad Boll Resuscitation and Emergency Talks 2023 Spezifische und regelmäßige Trainings für alle Profis entlang der Überlebenskette! These 6 der Bad Boller Reanimations und Notfallgespräche 2023 - Schröder, H.; Gräsner, J. T.; Metelmann, B.; Dormann, H. (Anästhesiologie & Intensivmedizin, 2023)
All professionals involved in health care should have knowledge and skills in basic cardiopulmonary resuscitation. In addition, it is necessary that the professional groups that are regularly confronted with cardiac arrest patients in the complex care settings of ambulance services, emergency rooms, cardiac catheter laboratory or intensive care units regularly train the advanced resuscitation measures, communications and care at the interfaces as a team in order to maintain a high standard of medical care.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Bad Boll Resuscitation and Emergency Talks; Cardiac Arrest; Interface Communication; Quality of Care; Training